The exponential age distribution and the Pareto firm size distribution - Alex Coad (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
Recent work drawing on data for large and small firms has shown a Pareto distribution of firm size. We mix a Gibrat-type growth process among incumbents with an exponential distribution of firm's age, to obtain the empirical Pareto distribution.
Keywords: L20; L25; 330; Firm size distribution; firm growth; Gibrat's law; Pareto distribution; Zipf Law; Betriebsgrößenstruktur; Statistische Verteilung; Publikationsanalyse; Unternehmenswachstum; Unternehmensentwicklung; Theorie